The complete mitogenome of the Australian tadpole shrimp Triops australiensis (Spencer & Hall, 1895) (Crustacea: Branchiopoda: Notostraca). (3rd May 2016) - Gan, Han Ming; Tan, Mun Hua; Lee, Yin Peng; Austin, Christopher M.
Abstract: The mitochondrial genome sequence of the Australian tadpole shrimp, Triops australiensis is presented (GenBank Accession Number: NC_024439) and compared with other Triops species. Triops australiensis has a mitochondrial genome of 15, 125 base pairs consisting of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs, and a non-coding AT-rich region. The T. australiensis mitogenome is composed of 36.4% A, 16.1% C, 12.3% G and 35.1% T. The mitogenome gene order conforms to the primitive arrangement for Branchiopod crustaceans, which is also conserved within the Pancrustacean.